Different facets of COVID-19-related stress in relation to emotional well-being, life satisfaction, and sleep quality - Saalwirth, Christina; Leipold, Bernhard (Frontiers in Psychology, 2023)
As the COVID-19 pandemic has shown, it is of great importance to investigate how people can maintain their mental health during chronically stressful times. This study therefore investigated which facets of COVID-19-related stress (Fear of COVID-19, financial worries, and social isolation) impacted people the most during a third COVID-19 infection wave from March until May 2021 and how these facets relate to well-being (emotional well-being and life satisfaction) and sleep quality. A study sample of 480 German participants (Mage = 43, SDage = 13.7, 20-69 years, 50.8% female) completed a cross-sectional online questionnaire. As predicted, social isolation was reported most often, followed by fear of COVID-19 and financial worries. In accordance with our expectations more social isolation and financial worries predicted lower emotional well-being and sleep quality. In contrast to our hypothesis, fear of COVID-19 only predicted emotional well-being and not sleep quality. Life satisfaction was solely predicted by financial worries and not by social isolation and fear of COVID-19, which only partly confirmed our hypotheses. These associations remained stable after controlling for age, gender, household income, and living alone. Financial worries, although reported the least often, were the strongest and most stable predictor for emotional well-being, sleep quality, and life satisfaction. Implications for future research and practice are discussed.